Lead concentration in hard dental tissues: SEM/EDS analysis - Kuzmanović-Radman Irena; Arbutina Adriana; Josipović Renata; Đeri Aleksandra (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Currently, one of the most important ecological issues is exposure to lead in environment, since it is a metal with evident toxic effects on human organism. Hard dental tissues are suitable structures for assessing long-term effects of exposure to toxic metals. The aim of this paper was to determine the concentration of lead in hard dental tissues of a rat with experimentally induced DM using SEM/EDS analysis, after 14 and 30 days of exposing animals to lead. Material and methods The study was conducted in rats of Wistar strains divided into the three groups. The first group consisted of 8 rats (128 molars and premolars of the upper and lower jaws) with experimentally induced DM, taking lead in the course of 14 days at the concentration of 1500 ppm; the second group included 8 rats (128 molars and premolars of the upper and lower jaws) taking lead in the course of 30 days at the concentration of 1500 ppm, while the third control group consisted of 5 healthy rats (80 molars and premolars of the upper and lower jaws). Experimental animals received lead-acetate every day at the concentration of 1500 ppm via water ad libitum. In these animals, diabetes mellitus was induced by Alloxan. The teeth samples were analysed using scanning electron microscopy (SEM). EDS analysis determined the mass fraction of lead and other elements in hard dental tissues. Results No lead was detected in a single tooth layer in the teeth of rats that received lead in drinking water in the course of 14 days. The average values of the mass fraction of lead, calcium, and phosphorus in enamel of teeth of rats receiving lead in the course of 30 days amounted to: lead 0.36%, calcium 15.48%, and phosphorus 10.62%. Lead was registered only in enamel. Conclusion Lead was detected in enamel only in rats receiving lead in the course of 30 days while it was not detected in teeth after the course of 14 days.